2005
DOI: 10.1242/dev.02142
|View full text |Cite
|
Sign up to set email alerts
|

Sim1andSim2are required for the correct targeting of mammillary body axons

Abstract: The mammillary body (MB), and its axonal projections to the thalamus(mammillothalamic tract, MTT) and the tegmentum (mammillotegmental tract,MTEG), are components of a circuit involved in spatial learning. The bHLH-PAS transcription factors SIM1 and SIM2 are co-expressed in the developing MB. We have found that MB neurons are generated and that they survive at least until E18.5 in embryos lacking both Sim1 and Sim2(Sim1-/-;Sim2-/-). However, the MTT and MTEG are histologically absent in Sim1-/-;Sim2-/- embryos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 45 publications
3
54
0
Order By: Relevance
“…This roughly conserved sim1 mRNA expression pattern suggests an important role for sim1 in posterior diencephalon and midbrain development. Although no specific defects were reported in these areas of Sim1 knockout mice, Sim1/ Sim2 double knockout mice have significant defects in axon targeting of mammillary body axons (Marion et al, 2005). Given the conserved expression patterns between zebrafish sim1 and mouse Sim1, the role of zebrafish sim1 in axonal development in the posterior diencephalon may also be conserved.…”
Section: Discussionmentioning
confidence: 96%
“…This roughly conserved sim1 mRNA expression pattern suggests an important role for sim1 in posterior diencephalon and midbrain development. Although no specific defects were reported in these areas of Sim1 knockout mice, Sim1/ Sim2 double knockout mice have significant defects in axon targeting of mammillary body axons (Marion et al, 2005). Given the conserved expression patterns between zebrafish sim1 and mouse Sim1, the role of zebrafish sim1 in axonal development in the posterior diencephalon may also be conserved.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, mammillary axons are rerouted toward the midline in Sim1/Sim2 null mice, possibly because of abnormal Robo3 expression (Marion et al, 2005).…”
Section: Transcriptional Regulationmentioning
confidence: 99%
“…Robo3 expression is also upregulated in a subset of mammillary neurons of the hypothalamus of mouse embryos deficient for the basic helix-loop-helix (bHLH) transcription factors Sim1 and Sim2 (Marion et al, 2005). Interestingly, mammillary axons are rerouted toward the midline in Sim1/Sim2 null mice, possibly because of abnormal Robo3 expression (Marion et al, 2005).…”
Section: Transcriptional Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Sim mutant analysis showed that Sim1 acts upstream of Sim2 and partially compensates for the loss of Sim2 in PVN embryonic development (Michaud et al, 1998, Goshu et al, 2002, Goshu et al, 2004. However, mSim1 and mSim2 act along compensatory pathways in mammillary body axonal development (Marion et al, 2005).…”
Section: Limb Sim1 Expression In Chick and Mouse Embryosmentioning
confidence: 99%